Evaluation of Fiber Content Based on Palm Plantation which Has Fermentation with Probiotic MOIYL - Yunilas Yunilas; Lili Warly; Yetty Marlida; Irsan Riyanto (Variabel, 2018)
Probiotic MOIYL is a probiotic that contains lignocellulolytic microorganisms derived from palm oil waste consist of Bacillus sp YLB1, Trichoderma sp YLF8 and Saccharomyces sp YLY3 which are potential in degrading fibers. This study aims to determine the effect of MOIYL probiotic use of palm oil waste based on fiber fraction content (NDF, ADF and lignin). This research is using Completely Randomized Design (RAL) factorial pattern 3 x 4 treatment with 3 replications. Factor I (various levels of palm oil waste substrate) and Factor II lcombination of mixed inoculum or cocktail inoculum indigenous microorganisms). Parameters observed included neutral detergent fiber (NDF), acid detergent fiber (ADF) and lignin. The results showed that the use of MOIYL probiotic in fermentation had a very significant effect (P <0.01) decrease NDF, ADF and lignin waste palm plantation. Probiotic MOIYL-based waste oil plays a role in degrading fiber (NDF, ADF and lignin) and can be used as a source of fermentation inoculum.